PHILOSOPHICAL THOUGHT OF AL-KINDI AND AL-FARABI - Mursidin, Ida Ilmiah (IAIN Bone, 2020)
This study has two purposes, both are: 1) To describe Al-Kindi's thoughts about the harmony between philosophy and religion, and the theory of divine philosophy. 2) To describe Al-Farabi's thoughts about the theory of emanation, and the theory of divinity. This research is using a qualitative method which its study focused on library research. Data sources used in this research are the works related to the two figures as well as other philosophical thought books. The results obtained from this study are; First, according to Al-Kindi, philosophy and religion make no difference because both are equally knowledgeable about truth. The function of philosophy is not to sue the truth of revelation, to demand superiority or to demand equality with revelation. Philosophy does not make a claim as the highest way to reach the truth and want to humble itself as a support for revelation. God theory according to him God is a form that actually does not come from nothing into existence, not preceded by other forms, could not be divided and there are no other substances that equal Him. Secondly, Al-Farabi about the emanations theory explained that God exists for the sake of His self. Through this research, it is expected to provide an understanding of the community about Muslim philosophy and its thoughts.